Parent-of-origin effects on complex traits in up to 236,781 individuals - Robin J. Hofmeister; Théo Cavinato; Roya Karimi; Adriaan van der Graaf; Fanny-Dhelia Pajuste; Jaanika Kronberg; Nele Taba; Andres Metspalu; Tõnu Esko; Mari Nelis; Georgi Hudjashov; Reedik Mägi; et al. (Nature, 2025)
Abstract Parent-of-origin effects (POEs) occur when the effect of a genetic variant depends on its parental origin 1 . Traditionally linked to genomic imprinting, POEs are believed to occur due to parental conflict over resource allocation to offspring, resulting in opposing parental influences 2 . Despite their importance, POEs remain underexplored in complex traits, owing to the lack of parental genomes. Here we present an approach to infer the parent of origin of alleles without parental genomes, leveraging interchromosomal phasing, mitochondrial and X chromosome data, and sex-specific crossover in siblings. Applied to the UK Biobank, this enabled parent-of-origin inference for up to 109,385 individuals. Genome-wide association study scans for 59 complex traits and over 14,000 protein quantitative trait loci contrasting maternal and paternal effects identified over 30 POEs and confirmed more than 50% of known associations. More than one third of these showed opposite parental influences, especially for traits related to growth (for example, IGF1 and height) and metabolism (for example, type 2 diabetes and triglyceride levels). Replication in up to 85,050 individuals from the Estonian Biobank and 42,346 offspring from the Norwegian Mother, Father and Child Cohort Study (MoBa) validated 87% of testable associations. Overall, our findings highlight the contribution of POEs to complex traits and support the parental conflict hypothesis, providing compelling evidence for this understudied evolutionary phenomenon.